Morphological features of the glomerular apparatus of fetuses and newborns kidneys in modeling different hypoxia. - Sorokina, I. V.; Markovsky, V. D.; Borzenkova, I. V.; Myroshnychenko, M. S.; Pliten, O. N. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Hypoxia of fetus and newborn is one of the actual problems of neonatology. The urinary system is one of the most susceptible to the adverse effects of hypoxia. Objective: to identify the morphological features of the glomerular apparatus of kidneys in fetuses and newborns at modeling different types of hypoxia. Methods. In this study chronic intrauterine hypoxia, acute postnatal hypoxia and mixed hypoxia were modeled on rats. Histological and morphometrical methods of investigation were used. The slides were studied on the microscope «Olympus BX-41». Digital data were processed using statistical methods of investigation. Results. Chronic intrauterine hypoxia and mixed hypoxia lead to a decrease of the glomeruli number in kidneys of fetuses and newborns and slowdown of the maturation of the glomeruli. Acute postnatal hypoxia does not affect the number of glomeruli in kidneys of fetuses and newborns. Conclusion. Quantitative changes of the glomerular apparatus of the kidneys in fetuses and newborns arising as a result of negative effect of chronic intrauterine and mixed hypoxia can lead in future to the development of various nephrology pathology in such children.